PLANNED OBSOLESCENCE AND CHILD CONSUMERISM IN THE BRAZILIAN LEGAL SYSTEM (CIPEEX, 2026)
The present research aims to analyze the impacts of planned obsolescence on child consumerism from the perspective of Brazilian law. It begins with the understanding that children are highly vulnerable to advertising strategies, being exposed from an early age to a market logic oriented toward the constant replacement of goods. Based on a literature review, the study discusses the relationship between corporate interests, targeted marketing, and the child’s fundamental right to full protection, as established in the Federal Constitution, the Consumer Protection Code, and the Statute of the Child and Adolescent. The findings reveal that abusive advertising directed at children, combined with the practice of planned obsolescence, undermines healthy child development and violates constitutional principles. The study therefore proposes a critical reflection on the role of law as an instrument to limit economic power and to guarantee ethical and sustainable consumption.
Keywords: planned obsolescence; child consumerism; publicity